The development of English computer aided education program for acquisition of color, number and shape concepts in preschool children without foreign language education background - BALABAN DAĞAL, ASUDE; ŞALLI, DUYGU; UYANIK, GÜLDEN; KANBUROĞLU, VOLKAN; BİRBİR, YAŞAR (ELSEVIER SCIENCE BV, 2015)
The impact of computers on children is seen as visual and audial. Visual effects on the screen is made by shapes and writings. Each new image on the screen carries a novelty for the child. Thus they act as a stimulator. Children, keeping up with the flow of information on the screen constantly intensify their attention and have to be warned in each new screenshot. Computer training lets the children learn through the play. Also it's an attractive tool for the children (Arici ve Demir, 2009). By reviewing the literature it can be said that small children can learn faster by the help of computer-assisted education. Therefore this study's purpose is to prepare a computer-assisted training programme to teach colors, numbers and shapes names in English to 60-72 months children who do not have any foreign language education and also do not know anything about foreign language. This study also aims to examine the impact of the prepared programme on the acquisition of basic foreign language concepts. The computer aided education programme includes basic English concepts like colors, numbers and shapes. A further objective of the study is to arouse curiosity of the children to different languages and to improve the children's awareness to other languages. 160 children participated in the research. Color, Number, Shape Names English Evaluation Form used to examine the children's knowledge about the color, number, shapes names in English before the programme and after the programme. As a result of the analysis, the developed computer-assisted training programme in English (color-number-shape) has been found effective in teaching English names of colors, numbers and shapes to the children who doesn't have any prior English knowledge. (C) 2015 The Authors. Published Elsevier Ltd.
Keywords: Computer aided language learning; english basic concepts